Iowa Birdline update, December 23, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for December 23, 1991. The highlights for the update include sightings of a Black-legged Kittiwake, Tundra Swan, Trumpeter Swan, Prairie Falcon, two species of gulls and a Golden Eagle. Also included are handwritten notes with sightings of a Northern Saw-whet Owl, large numbers of waterfowl on Rathbun Lake and a Lesser Black-backed Gull. Epson - sheet feed/flatbed